Akulturasi Islam dengan Tradisi Perkawinan Masyarakat Bangsawan Sasak (Studi di Kecamatan Kopang Kabupaten Lombok Tengah) - M. Najamudin Aminullah (PALAPA, 2017)
This study aims to study and describe the elements of Islam that is constructed in the implementation Sasak tradition, the tradition of aristocratic society wedding Kopang Sasak Lombok. Tradition, seen from the perspective of religious anthropology is part of human culture. By using anthropological approach, this study intends to reveal: how the process of marriage in society Sasak ?, How acculturation between Islam and the traditions of the community marital Duke Sasak, a character who acts and patterns of acculturation? The results of research show that the tradition of aristocratic society Sasak have room for Knowledge and value systems and behaviors that are reflected in the behavior of the deacon. His form is displayed through their own behavior, whether in the form of speech, reading, Busty-awenk (rules exist), symbols, especially on wedding traditions. The implementation of Sasak Kopang wedding tradition covers three parts. First: pre wedding or introductory period. Both marriage and marriage in the form of madrid, patience, and ngawinang. And third, in the form of wound post-wedding shoots (pisuke / gantiran), push the hand-over, ngongkolang and aji manners (value prices by social statafikasi). Sasak tradition is the formulation of local resources (local knowledge) in which there are indigenous traditions and elements of Islamic teachings that sifistikhumanistic. The elements constructed in the Sasak tradition are found in the customary values and behavior system of the tradition of marriage. And his family later to bring them into the family life of a harmonious, balanced (KAFA 'ah) and happy (saki nah, mawaddah, and mercy)